The transcatheter arterial chemoembolization combined with targeted nanoparticle delivering sorafenib system for the treatment of microvascular invasion of hepatocellular carcinoma. Issue 2 (20th December 2021) - Su, Dongna
ABSTRACT: to explore the value of transcatheter arterial chemoembolization (TACE) combined with targeted nanoparticle delivery system for sorafenib (SFB) to treat hepatocellular carcinoma (HCC) with microvascular invasion. 42 HCC patients with microvascular invasion after liver cancer surgery were selected from our hospital from December 2020 and February 2021. Patients were divided into experimental group and control group based on their willingness. Patients in experimental group (18 cases) were treated with combination therapy of TACE and Ab-SFB-NP system; while patients in control group (24 cases) took TACE and non-nano drug delivery system. There was no obvious difference in liver function and blood test results between two groups of patients before treatment and one month after treatment ( P > 0.05). Three months after treatment, differences of alanine aminotransferase (ALT) were statistically significant ( P < 0.05); while differences of other test results were not ( P > 0.05). The disease control rate (DCR) of patients in experimental group was higher slightly ( P > 0.05). The incidence of adverse reactions of patients in experimental group was lower than the control group and the differences were statistically significant ( P < 0.05). After three months of TACE, the DCR in the experimental group was significantly higher compared to control group. The toxic reactions of taking SFB with Ab-SFB-NP nano-drug delivery system mainly included hand-foot syndrome, diarrhea, and bleeding, the toxic reactions were mainly at level 1 2. After symptomatic treatment, the toxicity was effectively controlled, so the security was high.